„Spór o człowieka” a praktyka transplantacji. Na marginesie książki Marii Nowackiej "Etyka a transplantacje" - Bartoszek, Antoni; Matysik, Marcin (Śląskie Studia Historyczno-Teologiczne, 2004)
There has been an argument going on in the contemporary society about the nature of man. The quest for an answer to that question is growing more and more intense in the face of scientific and technological development. One of the branches of science, which provokes a discussion on its moral and anthropological character, is transplantology. Closely connected with this discussion is the book Ethics and Transplantations by Maria Nowacka. On one hand, these considerations outline her standpoint on the ethical dimension of such activities, and on the other hand, they embark on a discussion with her opinions. While Maria Nowacka argues that the application of transplantology is therealisation of the Cartesian philosophy, with its mechanistic view of human body, whereas the author of the article argues that transplantation is based upon an integral vision a person. At this point he emphasizes that the „informed consent” of donor is the prerequisite for taking a human organ to be morally right and to express human solidarity. The author also stresses that in the integral vision of human being as a bodily and spiritual unity, the human organism is the sign of a living man. The death of an organism as a whole is the sign of death of a human being. The death of an organism takes place only after the death of its integrating element, that is the brain. The author disagrees with Mrs. Nowacka’s opinion that a human being is a living organism which is actually or potentially conscious.According to the author the consciousness element is too much emphasized. The whole truth about man is that he is spirituallybodily unity. This holistic theory of a human person forms the basis of both philosophical system called personalism and the modern teaching of the Catholic Church.